Blood–Brain Barrier Dysfunction and the Potential Mechanisms in Chronic Cerebral Hypoperfusion Induced Cognitive Impairment - Xu, WenQing; Bai, Qingke; Dong, Qiang; Guo, Min; Cui, Mei (Frontiers in Cellular Neuroscience, 2022)
Chronic cerebral hypoperfusion (CCH) is a major cause of vascular cognitive impairment and dementia (VCID). While the underlying mechanisms have not been fully elucidated, the emerging data suggest that blood-brain barrier (BBB) dysfunction is one of the pivotal pathological changes in CCH. BBB dysfunction appears early in CCH, contributing to the deterioration of white matter and development of cognitive impairment. In this review, we summarize the latest experimental and clinical evidence implicating BBB disruption as a major cause of VCID. We discuss the mechanisms of BBB dysfunction in CCH, focusing on the cell interactions within the BBB, as well as the potential role of APOE genotype. In summary, we provide novel insights into the pathophysiological mechanisms underlying BBB dysfunction and the potential clinical benefits of therapeutic interventions targeting BBB in CCH.